Determination of Immunity T-cell Link State and Content of Cancer Stem Cells as Criterion to Estimate Efficiency of Preventive Breast Cancer Therapy with Cryopreserved Fetal Liver Cells - Goltsev, Anatoliy N.; Bondarovich, Nikolay A.; Kuznyakov, Andrey V.; Ostankov, Maksim V.; Ostankova, Lyudmila V.; Chelombit'ko, Olga V. (Problems of Cryobiology and Cryomedicine, 2014)
The expediency to use cryopreserved fetal liver cells (cFLCs) for preventive treatment of breast cancer (BC) is proved by a wide range of produced by them biologically active substances with immunomodulatory and antineoplastic activity. Revealing cancer stem cells (CSCs) in the mammary gland (MG) and determination of the immune system (IS) status are the methods of early diagnosis and evaluation of preventive treatment efficiency of breast cancer. The experiments were performed in 16-month-old C3H/He mice which in 6 months were injected by cryopreserved or native FLCs of 14 gestation days at a dose of 1Ã—106 or 5Ã—106 cells. Probl Cryobiol Cryomed 2014; 24(3):238-248.